Phương pháp giải một lớp bài toán quy hoạch nguyên có cấu trúc đặc biệt - Dũng, Võ Văn Tuấn; Thiệu, Trần Vũ (Journal of Computer Science and Cybernetics, 2016)
In this paper a finite algorithm for solving a class of integer problems with special structure is presented. It is based on techniques commonly used in solving transportation problems to improve feasible solutions. A technique for reducing the size of problems to be solved is also presented. Finally, some computational results are reported.